2013
DOI: 10.1371/journal.pone.0062992
|View full text |Cite
|
Sign up to set email alerts
|

The Confounding Effect of Population Structure on Bayesian Skyline Plot Inferences of Demographic History

Abstract: Many coalescent-based methods aiming to infer the demographic history of populations assume a single, isolated and panmictic population (i.e. a Wright-Fisher model). While this assumption may be reasonable under many conditions, several recent studies have shown that the results can be misleading when it is violated. Among the most widely applied demographic inference methods are Bayesian skyline plots (BSPs), which are used across a range of biological fields. Violations of the panmixia assumption are to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
306
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(318 citation statements)
references
References 30 publications
11
306
1
Order By: Relevance
“…Whether the recent population size decline (over last few hundreds of years) apparent in most mitochondrial lineages is a true signal potentially correlated with increasing human population sizes along the lake shore or simply a methodological artifact (Chikhi et al, 2010;Heller et al, 2013) remains unclear. It is also interesting to note that the TCS-1 haplotypes assigned to the pink haplotype cluster are not exclusive to the very northern part of the lake.…”
Section: Phylogeographic Patternsmentioning
confidence: 99%
“…Whether the recent population size decline (over last few hundreds of years) apparent in most mitochondrial lineages is a true signal potentially correlated with increasing human population sizes along the lake shore or simply a methodological artifact (Chikhi et al, 2010;Heller et al, 2013) remains unclear. It is also interesting to note that the TCS-1 haplotypes assigned to the pink haplotype cluster are not exclusive to the very northern part of the lake.…”
Section: Phylogeographic Patternsmentioning
confidence: 99%
“…The risk of such spuriously inferred population size changes has been reported previously (for example, Leblois et al, 2006;Stadler et al, 2009;Heller et al, 2013;Bosse et al, 2014) and the developers of the PSMC method also pointed out that if a population splits in half and later on merges again, even in the absence of demographic changes, an increase in effective population size can be observed (Li and Durbin, 2011). Heller et al (2013) showed how deviations from the random mating model affect demographic inferences using Bayesian skyline plots (BSP), a standard tool used for analysing mitochondrial DNA sequences.…”
mentioning
confidence: 68%
“…However, developments in sequencing technologies over the last decade have enabled researchers to produce data covering most, if not all, of the complete genome of a species relatively cheaply (for example, Groenen et al, 2012;Zhan et al, 2013), and estimate important evolutionary parameters using as few as a single genome, for example, the trend in effective population size over time (for example, Li and Durbin, 2011;Schiffels and Durbin, 2014). However, such methodologies assume that the data used for the analysis represent that of an unstructured population, and as it has been shown previously, deviations from that model can inflate estimates of the effective population size (Leblois et al, 2006;Heller et al, 2013;Bosse et al, 2014).…”
mentioning
confidence: 99%
See 2 more Smart Citations